2015
DOI: 10.1111/jace.13695
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Submicrometer‐Sized Ce:YAG Spherical Particles by Solvothermal Process Using Alcohol Solvents

Abstract: A rapid synthesis method for preparing homogeneous and submicrometer-sized cerium-doped yttrium aluminum garnet (Ce: YAG) particles was proposed in this work. Instead of precipitating the YAG amorphous precursor prior to the solvothermal process, cerium, yttrium, and aluminum nitrates were dissolved in alcoholic solvents to form transparent and clear solutions that were directly transferred into the stainless autoclave to undergo the solvothermal reaction. Four different alcohol solvents, that is, ethanol, 2-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Producing nano-sized Ce:YAG phosphors has been demonstrated by solution based synthesis approaches, such as the sol-gel method, co-precipitation method, ethanol-water solvothermal method, and glycothermal method. [13][14][15][16][17][18][19][20][21] However, the sol-gel and co-precipitation methods require calcination at elevated temperatures, whereas the solvothermal and glycothermal approaches provide crystallized YAG directly from solution with no further annealing required. Further, the hydrothermal method demands high pressures and long reaction times in order to produce phase-pure YAG.…”
Section: Introductionmentioning
confidence: 99%
“…Producing nano-sized Ce:YAG phosphors has been demonstrated by solution based synthesis approaches, such as the sol-gel method, co-precipitation method, ethanol-water solvothermal method, and glycothermal method. [13][14][15][16][17][18][19][20][21] However, the sol-gel and co-precipitation methods require calcination at elevated temperatures, whereas the solvothermal and glycothermal approaches provide crystallized YAG directly from solution with no further annealing required. Further, the hydrothermal method demands high pressures and long reaction times in order to produce phase-pure YAG.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous flow hydrothermal synthesis 12 is currently the fastest route for the synthesis of YAG nanoparticles with little agglomeration, however, the process requires quite aggressive conditions,~340°C and 27 MPa, which makes it expensive. The solvothermal route, however, opens up the opportunity to utilize different solvents to reduce the severity of the supercritical conditions required [13][14][15][16] and also offers greater control over particle characteristics by acting as an interfacial barrier between the crystallites during the process. * Our previous study on the conventional solvothermal synthesis of YAG nanoparticles suggested that a minimum of 270°C and 2 MPa was required for 2 hours to initiate the onset of formation of YAG.…”
Section: Introductionmentioning
confidence: 99%